Pelatihan penelitian tindakan kelas bagi mahasiswa Program Studi Pendidikan Bahasa Arab Jurusan Pendidikan Bahasa Asing FBS UNM - Ambo Dalle; Misnawaty Usman; Misnah Mannahali; Nurul Mukhlisah Abdal (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partners in this dedication activity are students of the Arabic Language Education Study Program, Department of Foreign Language Education, FBS UNM. The problem is: (1) Students have not been able to design class action research proposals, (2) Students have not been able to carry out classroom action research, (3) Facilitators who can direct problems in the learning process are still limited. The method used in counseling, training, simulation, and discussion. The results achieved are (1) Partner students have the ability to carry out making classroom action research; (2) Students already have the ability to make classroom action research; (3) Partner students who have attended training or counseling can be facilitators for students who have not participated in counseling. The implementation of the classroom action research training for students of the Arabic language study program was carried out as planned and the results achieved in the community partnership program activities could be categorized quite sufficiently. Community service activities are categorized as more than adequate (80%) because they are judged by the active participation of the participants in presenting the material which is generally motivated